Expression and functional characterization of FOXP3+ CD4+ regulatory T cells in ulcerative colitis. - Yu, Q; Saruta, M; Avanesyan, A; Fleshner, P; Banham, A; Papadakis, K (2007)
BACKGROUND: CD4+CD25+ regulatory T cells (TR) can prevent or treat experimental murine colitis but little is known about their potential role in human inflammatory bowel disease (IBD). FOXP3 is a transcription factor that plays a critical role in the development and function of CD4+CD25+ TR. The aim of this study was to examine the presence and functional characteristics of TR cells in colonic lymphoid tissues in patients with ulcerative colitis (UC). METHODS: FOXP3 expression was assessed by flow cytometry, immunohistochemistry, and reverse-transcriptase polymerase chain reaction (RT-PCR). Functional characterization of CD4+CD25+ cells was analyzed by suppression of proliferation and secretion of cytokines by cocultured effector CD4+CD25- T cells. RESULTS: FOXP3 +CD4+ T cells are increased in the lamina propria (LP) of inflamed and noninflamed areas of UC colon compared to normal colon. CD4+CD25+ T cells in UC mesenteric lymph nodes (MLN) express FOXP3 mRNA and protein and suppress the proliferation of autologous MLN CD4+CD25 T cells. The suppressor activity of MLN CD4+CD25+ T cells is cell contact-dependent but cytokine-independent. In addition, CD4+CD25+ T cells potently suppress the production of both Thl (IFN-gamma, IL-2) and Th2 (IL-5, IL-13) cytokines by cocultured CD4+CD25 T cells. FOXP3' cells localized in the T-cell-rich areas of MLN and occasionally present in the follicles. CONCLUSIONS: There is an expansion of FOXP3+CD4+ T cells in mucosal lymphoid tissues in UC. CD4+CD25+ isolated from UC MLN express FOXP3 and display features of TR cells in spite of active mucosal inflammation. These data suggest that their suppressor activity may be abrogated in vivo or they are unable to counterbalance the chronic mucosal inflammation in UC.